Drug lords and narco-corruption: the players change but the game continues - Lupsha, Peter A. (Crime, law and social change, 1991)
This article examines the patterns and history of drug trafficking related corruption in Mexico. While the Bush administration has the efforts of the Salinas administration to fight both drug trafficking and corruption the author concludes that merely the players have changed, while trafficking and high-level corruption continue.